Ecological Modeling of the Supraglacial Ecosystem: A Process-based Perspective - Stibal, Marek; Bradley, James A.; Box, Jason E. (Frontiers in Earth Science, 2017)
Glacier and ice sheet surfaces are important microbe-dominated ecosystems that are changing rapidly due to climate change, with potentially significant impacts. A theoretical framework of the supraglacial (glacier surface) ecosystem is needed to enable its mathematical modelling, a necessary tool for understanding, quantifying and predicting present day and future ecosystem dynamics. Here we review key biological processes occurring on glacier and ice sheet surfaces and present three frameworks for constructing process-based models of the surface ecosystem, using the largest supraglacial ecosystem on Earth – the Greenland ice sheet surface – as an important example. The models are based on organic carbon transformations, but vary in numerical complexity and in the level of detail of biological processes. This perspective is intended to guide future supraglacial ecosystem model development, field data collection for parameterisation and validation purposes, and encourage inter-disciplinary collaboration between modellers and experimentalists.